2015
DOI: 10.1088/0004-637x/812/2/99
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the Intermediate-Width Emission Line Region in Quasar Oi 287 With the Broad Emission Line Region Obscured by the Dusty Torus

Abstract: The existence of intermediate-width emission line regions (IELRs) in active galactic nuclei has been discussed for over two decades. A consensus, however, is yet to be arrived at due to the lack of convincing evidence for their detection. We present a detailed analysis of the broadband spectrophotometry of the partially obscured quasar OI 287. The ultraviolet intermediate-width emission lines (IELs) are very prominent, in high contrast to the corresponding broad emission lines (BELs) which are heavily suppress… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 57 publications
2
34
0
Order By: Relevance
“…We picked them up again during the series study of the reddening AGNs (e.g., Li et al 2015;Liu et al 2016;Pan et al 2017;Zhang et al 2017). We study the He I* λ10830 absorption lines (the first detection reported by Leighly et al 2011) as well as the continuum, and hydrogen Balmer/Paschen broad emission lines of these objects.…”
Section: Introductionmentioning
confidence: 99%
“…We picked them up again during the series study of the reddening AGNs (e.g., Li et al 2015;Liu et al 2016;Pan et al 2017;Zhang et al 2017). We study the He I* λ10830 absorption lines (the first detection reported by Leighly et al 2011) as well as the continuum, and hydrogen Balmer/Paschen broad emission lines of these objects.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Crenshaw et al (2009) detected ILR emission with width of 680 km s −1 in the historically low state spectrum of NGC 5548 obtained with the Space Telescope Imaging Spectrograph on the Hubble Space Telescope. Using the HST/ FOS spectra of quasar OI 287, Li et al (2015) reported the detection of intermediate width emission lines originating at a distance of ∼ 2.9 pc from the central black hole. The question remains unanswered, is there any separation between gas responsible for broad and narrow line emission in different types of AGN?…”
Section: Introductionmentioning
confidence: 99%
“…DiPompeo et al 2014a;Runnoe et al 2014;Brotherton, Singh & Runnoe 2015;Stalevski et al 2016) and in the presence of an axis-symmetric dust distribution (the so-called "dusty-torus"), orientation alone has the potential to unify obscured and unobscured quasars, as it largely has for Seyfert galaxies (e.g. Antonucci 1993;Stalevski et al 2012;Ichikawa et al 2015;Gratadour et al 2015;Mason 2015;Netzer 2015;Siebenmorgen, Heymann & Efstathiou 2015;Li et al 2015;Wylezalek et al 2016;Obied et al 2016). On the other, attempts to explain the driving of gas into nuclear regions in order to fuel the supermassive black hole (SMBH) have resulted in models that link quasar activity to major galaxy mergers and a general evolutionary sequence (e.g.…”
Section: Introductionmentioning
confidence: 99%